An Emerging Framework of Inclusion - Colette Saldanha; Elina Hankela (African Journal of Gender and Religion (AJGR))
The article outlines a grounded framework for considering and working towards inclusion in ecclesial contexts in and beyond South Africa. This framework is based on stories gathered through a qualitative study among non-ordained women in two parishes of the Anglican Church in Southern Africa in the Diocese of Johannesburg. Five elements of inclusion that make up the framework emerged in the analysis of the data: acceptance, community, choice, voice and support. As these elements are discussed, using an intersectional lens, attention is drawn to factors that strengthen or weaken the sense of inclusion in this particular context. The use of this lens further highlights the need to read the framework in context, focusing on factors that are important to the people themselves, but also those factors that for some reason are not engaged by the community in question.